Forced vibration analysis of a fiber reinforced composite beam - Akbaş, Şeref Doǧuşcan (Techno-Press, 2021)
In this study, forced vibration analysis of a fiber reinforced composite cantilever beam is investigated under a harmonic load. In the beam model, the Timoshenko beam theory is used. The governing equations of problem are derived by using the Lagrange procedure. In the solution of the problem the Ritz method is used and algebraic polynomials are used with the trivial functions for the Ritz method. In the solution of the forced vibration problem, the Newmark average acceleration method is used in the time history. In the numerical examples, the effects of fibre orientation angles, the volume fraction and dynamic parameters on the forced vibration response of fiber reinforced composite beam are presented and discussed.
Keywords: fiber reinforced composite materials; forced vibration analysis; Ritz Method; Timoshenko Beams